2011
DOI: 10.1007/s11248-011-9501-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional ability of cytoskeletal β-actin regulator to drive constitutive and ubiquitous expression of a fluorescent reporter throughout the life cycle of transgenic marine medaka Oryzias dancena

Abstract: Marine medaka Oryzias dancena, a candidate model organism, represents many attractive merits as a material for experimental transgenesis and/or heterologous expression assay particularly in the field of ecotoxicology and developmental biology. In this study, cytoskeletal β-actin gene was characterized from O. dancena and the functional capability of its promoter to drive constitutive expression of foreign reporter protein was evaluated. The O. dancena β-actin gene possessed a conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 65 publications
8
43
1
1
Order By: Relevance
“…EGFP expression continued throughout adulthood as determined at the age of 7 months (not shown). This is in agreement with recent studies in zebrafish and medaka showing EGFP expression under the control of different b-actin promoters to be active in numerous tissues of adult fish (Burket et al, 2008;Cho et al, 2011). In this particular experiment we obtained four potential founders from 350 injected oocytes indicating a very low efficiency of around 1%.…”
Section: Developmental Dynamicssupporting
confidence: 92%
See 1 more Smart Citation
“…EGFP expression continued throughout adulthood as determined at the age of 7 months (not shown). This is in agreement with recent studies in zebrafish and medaka showing EGFP expression under the control of different b-actin promoters to be active in numerous tissues of adult fish (Burket et al, 2008;Cho et al, 2011). In this particular experiment we obtained four potential founders from 350 injected oocytes indicating a very low efficiency of around 1%.…”
Section: Developmental Dynamicssupporting
confidence: 92%
“…Analysis of EGFP expression revealed that all four larvae showed a mosaic expression pattern of EGFP as it has been frequently described for the founder generation of transgenic animals ( Fig. 3C,D ;Winkler et al, 1991;Hosemann et al, 2004;Cho et al, 2011). EGFP expression continued throughout adulthood as determined at the age of 7 months (not shown).…”
Section: Developmental Dynamicssupporting
confidence: 67%
“…The functional ability of the β-actin regulator to drive ubiquitous expression of the red fluorescent reporter in this fish species has been described previously (Cho et al, 2011). Details of the expression patterns of the endogenous β-actin gene, as well as the β-actin promoterdriven RFP expression in marine medaka, were provided in our previous work (Cho et al, 2011). The β-actin-driven fluorescent signal in transgenic marine medaka usually becomes clearly visible by the embryonic stage (onset often occurs at late gastrulation), with the RFP phenotype lasting persistently to adulthood.…”
Section: Transgenic Strainsmentioning
confidence: 97%
“…Various transgenic marine medaka founders were generated by the microinjection of a fluorescent reporter construct consisting of the RFP gene (DsRed2; Clontech Laboratories Inc., Mountain View, CA, USA) under the control of endogenous β-actin regulator (podβ-actRFP; Cho et al, 2011). Microinjection was performed on one-cell embryos using the ClaI-linearized podβ-actRFP construct suspended at a concentration of 50 μg/ml.…”
Section: Transgenic Strainsmentioning
confidence: 99%
See 1 more Smart Citation